The Effect of Practicum Activities on Improving Data Literacy for High School Students - Rahmawati, Dewi; Rusilowati, Ani; Hardyanto, Wahyu (Physics Communication, 2021)
The world change in the industrial revolution 4.0 is the state of the industry in the 21st century that combines automation and cyber technology. Education is one of the fields that is experiencing the impacts of the changes in the industrial revolution 4.0. The skills needed in this era was the literacy skills consisting of three new literacys, namely data, technological, and human literacy. The purpose of this study was to determine the effect of practicum activities on increasing data literacy of high school students. The method used in this study was a mix method with a concurrent embedded design, while the experimental design used was a one group pretest-posttest design. The instrument used was a written test with 10 numbers to get a pretest-posttest score. The pretest-posttest scores were used to measure the improvement of students' data literacy. The results of data analysis using the t-test paired samples t-test obtained the average value of the pretest and posttest scores significantly different with the value of tcount ttable that is 4.770 2.042 with an effect size of 0.83. It can be concluded that there is an effect of practicum activities on increasing data literacy of high school students with high categories.